The programming historian (Editorial Board of the Programming Historian, 2012)
Offers novice-friendly, peer-reviewed tutorials that help humanists learn a wide range of digital tools, techniques, and workflows to facilitate their research.
Keywords: Digital humanities; Electronic information resources : Management; Python (Computer program language)